Multicenter, retrospective, cohort study shows platelet counts predict hepatocellular carcinoma development in patients with nonalcoholic fatty liver disease. Issue 5 (17th February 2023) - Fujii, Hideki; Fujii, Makoto; Iwaki, Michihiro; Hayashi, Hideki; Toyoda, Hidenori; Oeda, Satoshi; Hyogo, Hideyuki; Kawanaka, Miwa; Morishita, Asahiro; Munekage, Kensuke; Kawata, Kazuhito; Tsutsumi, Tsubasa; et al.
Abstract: Aim: Impacts of platelet counts at the time of liver biopsy on hepatocellular carcinoma (HCC) development in patients with nonalcoholic fatty liver disease (NAFLD) remain unknown. The aim of this study was to investigate the prognostic value of platelet counts in patients with biopsy‐confirmed NAFLD using data from a multicenter study. Methods: One thousand three hundred ninety‐eight patients were included in this subanalysis of the CLIONE (Clinical Outcome Nonalcoholic Fatty Liver Disease) in Asia study. Liver biopsy specimens were pathologically diagnosed, and histologically scored using the NASH Clinical Research Network system. Demographic, clinical, laboratory, and pathological data were collected. Results: During a median follow‐up period of 4.6 years (range, 0.3–21.6 years), which corresponds to 8874 person‐years, 37 patients developed HCC. Using a cut‐off baseline platelet count of 192 × 109/L, the lower platelet group had a higher HCC rate than the higher platelet group (6.7% vs. 0.4%; p < 0.001). This cut‐off value significantly stratified the event‐free rate for HCC. Lower platelet counts were associated with an increased risk of HCC development. Relative to patients with platelet counts of 192 × 109/L, patients with platelet counts of 100 × 109/L had an unadjusted hazard ratio (HR) for HCC development of 7.37 (95% confidence interval [CI], 3.81–14.2) and an adjusted HR of 11.2 (95% CI, 3.81–32.7; p < 0.001), adjusting for age, sex, NASH,  and diabetes. Conclusions: Baseline platelet counts of 192 × 109/L and lower are associated with a higher risk of developing HCC in patients with biopsy‐confirmed NAFLD and require active surveillance. Abstract : Platelet counts less than 192 × 109/L should be included in active surveillance to identify biopsy‐confirmed nonalcoholic fatty liver disease‐derived hepatocellular carcinoma.